Assessment of tick populations associated with capybaras in natural reserves and human-modified environments with or without invasive plants in the state of São Paulo, Brazil - Matheus Pasini-Martins; Rubia Diaz Taveiros Kuhne; Carolina Moura de Oliveira; Lina C. Binder; Igor S. Silito; Adriano Pinter; Fernanda B. Passos Nunes; Thiago F. Martins; José Henrique de Hildebrand e Grisi Filho; Wayne Dawson; Philip A. Stephens; Dalva Maria da Silva Matos; et al. (Experimental and Applied Acarology, 2026)
In southeastern Brazil, capybaras ( Hydrochoerus hydrochaeris ) are main hosts of the ticks Amblyomma dubitatum and Amblyomma sculptum ; the latter has great medical importance for being the main vector of Rickettsia rickettsii , the agent of Brazilian spotted fever (BSF). This study aimed to quantify ticks in areas invaded and not invaded by exotic plants ( Hedychium coronarium , Cenchrus purpureus or Megathyrsus maximus ) within capybaras’ living areas in São Paulo state. Tick populations were quantified in 24 capybara habitats, eight in natural reserves and 16 human-modified landscapes; the latter were composed of eight BSF-endemic areas and eight BSF-nonendemic areas. In the 24 areas, ticks were sampled in plots of natural forests and plots with at least one of the three invasive plants. Both presence and density of A. sculptum were higher in human-modified landscapes, while the presence and density of A. dubitatum tended to be similar among human-modified landscapes and natural reserve areas. The two tick species were collected both in areas colonized by invasive plants ( H. coronarium , M. maximus , and/or C. purpureus ) and in areas of non-invaded vegetation. However, a higher density of A. dubitatum was observed in areas of H. coronarium and a lower density of A. sculptum in this type of vegetation. Within human-modified landscapes, there was a higher density of A. sculptum in BSF-endemic areas when compared to non-endemic areas, unlike A. dubitatum , which remained at an almost constant density and presence among BSF-endemic and non-endemic areas. Plant invasions may have some role in the ecology of capybara-associated ticks.

A high gene flow in populations of Amblyomma ovale ticks found in distinct fragments of Brazilian Atlantic rainforest - Gislene F. S. R. Fournier; Adriano Pinter; Renata Santiago; Sebastian Muñoz-Leal; Thiago Fernandes Martins; Marcos Gomes Lopes; Karen D. McCoy; Celine Toty; Mauricio C. Horta; Marcelo B. Labruna; Ricardo A. Dias (Experimental and Applied Acarology, 2019)

Ticks collected on birds in the state of São Paulo, Brazil - Marcelo B. Labruna; Luiz F. Sanfilippo; Cristiane Demetrio; Ana C. Menezes; Adriano Pinter; Alberto A. Guglielmone; Luis F. Silveira (Experimental and Applied Acarology, 2007)

Ticks (Acari: Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Matias P. J. Szabó; Marcelo B. Labruna; Karina C. Castagnolli; Marcos V. Garcia; Adriano Pinter; Viviane A. Veronez; Geórgia M. Magalhães; Márcio B. Castro; Alexandre Vogliotti (Experimental and Applied Acarology, 2006)

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

Life cycle of Amblyomma cooperi (Acari: Ixodidae) using capybaras (Hydrochaeris hydrochaeris) as hosts - Marcelo B. Labruna; Adriano Pinter; Rodrigo H.F. Teixeira (Experimental and Applied Acarology, 2004)

Life cycle and host specificity of Amblyomma triste (Acari: Ixodidae) under laboratory conditions - Marcelo B. Labruna; Eric Y.M. Fugisaki; Adriano Pinter; José Maurício B. Duarte; Matias J.P. Szabó (Experimental and Applied Acarology, 2003)

Life-cycle and host specificity of Amblyomma tigrinum (Acari: Ixodidae) under laboratory conditions - Marcelo B. Labruna; Silvio L.P. Souza; Ana C. Menezes; Maurício C. Horta; Adriano Pinter; Solange M. Gennari (Experimental and Applied Acarology, 2002)

Ticks (Acari: Ixodidae) Associated with Domestic Dogs in Franca Region, São Paulo, Brazil - Matias Pablo Juan szabó; Tiago Marquez Cunha; Adriano Pinter; Fernando Vicentini (Experimental and Applied Acarology, 2001)